Fuzzy Inventory Model for Imperfect Items with Price Discount and Penalty Maintenance Cost - V. Kuppulakshmi, V. Kuppulakshmi; C. Sugapriya, C. Sugapriya; J. Kavikumar, J. Kavikumar; D. Nagarajan, D. Nagarajan (Hindawi, 2023)
Te present paper considers the fuzzy economic manufacturing model (FEMM) for an inventory model with an imperfect production process that has been studied along with rework. During the pandemic, it is evident that the products accumulated without a sale, which has increased the maintenance cost of the products. Tis research paper compares a special sale of products with discount and without discount prices both in the fuzzy environment and in the crisp case. New computing methods based on fuzzy logic are being utilized to enhance identifcation, decision making, and optimization. A triangular fuzzy number is applied in the economic production quantity to emphasize the importance of optimal manufacturing. Te EPQ model’s optimal total cost is obtained in the crisp version. It is to be noted that this model is developed in the fuzzy sense by using the deterioration as a triangular fuzzy number. Te applications of this model in the felds are constructing customized industrial machinery or heavyduty construction equipment, specifc chemicals, and processed food. By using MATLAB R2021, a numerical example of the optimal solution is provided. Finally, the present research discusses how changing several parameters afects the optimum total cost.